The use of stable isotopes for the characterisation of natural organic matter and investigation of the different organic precursors of aquatic systems - White, Dawn Elaine (Curtin University, 2013)
This study assesses the potential of compound specific stable carbon isotope analysis (CSIA) to complement traditional molecular analysis and to improve the overall characterisation of Natural Organic Matter (NOM) in drinking water systems. CSIA for characterising NOM fractions and for following their fate from catchment to tap is examined here on a range of samples, including contrasting surface reservoir NOM, biofoulants from water treatment filtration membranes and biofilms from distribution systems.